Meningkatkan Kreatifitas Seni Rupa Anak Usia Dini Melalui Kegiatan Menggambar, Menggunting Dan Menempel (3M) di Raudhatul Athfal Nurul Yaqin Desa Simpang Sungai Duren Jambi - Ariana Dwita; Siti Mariah Ulfa; Anisah (Alzam: Journal of Islamic Early Childhood Education, 2026)
This study aims to improve children's visual arts creativity through drawing, cutting, and pasting activities. The research was conducted using the Classroom Action Research (CAR) method, consisting of a pre-cycle, Cycle I, and Cycle II. The subjects of the study were 32 children. The results of the pre-cycle showed that the children’s visual arts creativity was still low, with 24 children (75%) categorized as Not Yet Developed (NYD), 5 children (16%) as Beginning to Develop (BD), 3 children (9%) as Developing as Expected (DE), and no children achieving the Very Well Developed (VWD) category. In Cycle I, Meeting I, there was an improvement: 11 children (34%) were in the NYD category, 9 children (28%) in BD, 7 children (22%) in DE, and 5 children (16%) in VWD. Further improvement was observed in Cycle I, Meeting II, with 3 children (9%) in NYD, 5 children (9%) in BD, 15 children (47%) in DE, and 9 children (28%) in VWD. In Cycle II, Meeting I, no children remained in the NYD or BD categories; 19 children (59%) were categorized as DE and 13 children (41%) as VWD. The most significant improvement was achieved in Cycle II, Meeting II, where all children reached the developed categories: 2 children (6%) were in the DE category and 30 children (94%) achieved the VWD category.